Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1996
DOI: 10.1115/96-gt-447
|View full text |Cite
|
Sign up to set email alerts
|

Solid Oxide Fuel Cell Combined Cycles

Abstract: The integration of the solid oxide fuel cell (SOFC) and combustion turbine technologies can result in combined-cycle power plants, fueled with natural gas. that have high efficiencies and clean gaseous emissions. Results of a study are presented in which conceptual designs were developed for three power plants based upon such an integration, and ranging in rating from 3 to 10 MW net ac. The plant cycles are described, and characteristics of key components are summarized. In addition, plant design-point efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
5
8
0
Order By: Relevance
“…The performance of the recuperator is as detailed in Table 2. This cycle is similar to those described by Bevc et al (1996), Nathanson (1996), Ali and Moritz (1996) and White (1996). Perhaps the most significant aspect of these results is that the peak efficiency is only slightly greater, by around 1% point, than that obtained with the unrecuperated cycle.…”
Section: Bii Fuel Cell Plus Recuperated Gassupporting
confidence: 88%
See 2 more Smart Citations
“…The performance of the recuperator is as detailed in Table 2. This cycle is similar to those described by Bevc et al (1996), Nathanson (1996), Ali and Moritz (1996) and White (1996). Perhaps the most significant aspect of these results is that the peak efficiency is only slightly greater, by around 1% point, than that obtained with the unrecuperated cycle.…”
Section: Bii Fuel Cell Plus Recuperated Gassupporting
confidence: 88%
“…The component efficiencies used in the model we likely to be slightly optimistic in predicting the performance of some existing small industrial gas turbines. However, they represent a realistic target for new turbines and are consistent with those used elsewhere (Bevc et al, 1996). ,…”
Section: Pz Lannsupporting
confidence: 82%
See 1 more Smart Citation
“…2) were used as input for the SOFC+GT model, providing point-by-point the corresponding performances of the SOFC+GT cycle. Previous works have shown the possibility of obtaining net electrical efficiencies up to 75% (LHV) for medium or large scale (>100MW) power plants adopting advanced gas turbines and SOFC systems with configurations similar or more complex than the cycle represented in Fig 8: these plants benefit of both advanced CT cycles (intercooled, regenerative, reheated cycles) and the advantage of adopting high efficiencY turbomachines (Stephenson and Ritchey, 1997), often with the addition of complex heat recovery bottoming cycles (Bevc et al,1996;Campanari andMacchi, 1998, Lobachyov andRichter, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The term 'hybrid' has been introduced herein to indicate the integration of pressurized solid oxide fuel cells (PSOFC) into a standard Brayton cycle [4], Recently, successful trials of a 100 kW plant [5] with internal reforming of natural gas feed have demonstrated this concept and attracted interest into larger applications for distributed power generation, e.g. 1 MW [6] and 20 MW range [4], These larger hybrid systems have been analyzed and studied extensively over the past five years [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%